Green solvent-assisted development of UV-spectrophotometric and RP-HPLC methods for telmisartan and efonidipine HCl ethanolate - M. S. Kotkar; S. B. Dighe; M. F. Ansari; S. P. Mankar; R. K. Godge (Creative Pharma Assent, 2026)
Background: Hypertension is a prevalent cardiovascular disorder requiring effective therapeutic strategies. Telmisartan, an angiotensin II receptor antagonist, and Efonidipine HCl Ethanolate, a calcium channel blocker, are often co‑administered for synergistic blood pressure control. To ensure the quality and efficacy of pharmaceutical formulations, it is essential to develop simple, precise, and eco-friendly analytical methods for their simultaneous estimation and validation in accordance with ICH Q2(R1) guidelines. Methodology: Two UV spectroscopic methods and one RP‑HPLC method were developed and validated. Method A employed the simultaneous equation approach using absorbance values at 297 nm and 251 nm, corresponding to the λmax of Telmisartan and Efonidipine, respectively. Method B utilized the area under the curve (AUC) method for simultaneous quantification. The RP‑HPLC method was performed on an Agilent C18 column (250 × 4.6 mm, 5 μm) with isocratic elution using ethanol and 0.1% orthophosphoric acid in water (85:15 v/v) at a flow rate of 0.9 mL/min, and detection was at 253 nm. Results and Discussion: All three methods demonstrated excellent linearity, precision, and accuracy within validated ranges. Recovery studies confirmed reliability, with values within acceptable limits. The UV method (Greenness score 92) is slightly greener than HPLC (Greenness score 88), with both demonstrating excellent eco-friendly performance. The UV methods offer rapid and economical screening, while RP‑HPLC ensures high sensitivity and specificity. The use of ethanol as a green solvent supports eco‑friendly pharmaceutical analysis. Conclusion: Validated UV and RP‑HPLC methods were successfully developed for simultaneous estimation of Telmisartan and Efonidipine HCl Ethanolate. These approaches are robust, precise, economical, and environmentally sustainable for routine quality control in pharmaceutical dosage.